Effect of selection methods on seed potato quality in the following season. Issue 1 (November 2021) - Gunadi, N; Pronk, A; Kartasih, A A; Prabaningrum, L; Moekasan, T K; Hengsdijk, H
Abstract: Most potato farmers in Indonesia select the small tubers at harvest for planting in the following season, the so-called farmers' practice (FP). This propagation method is cheap, but the small tubers may come from less healthy plants, which increases the build-up of diseases with accelerated yield decreases over the seasons. Alternatively, farmers may identify healthy plants within the growing season and select those for propagation, the so-called positive plant selection method (PPSM). An experiment was carried out to evaluate the effects of PPSM compared to FP on yields in the following season in the two main potato growing areas of West Java, i.e., Pangalengan and Garut. Generations G2 and G3 of cv. Granola and one generation of the imported cv. Atlantic were used. Selected seeds using PPSM and FP were planted in the second season in a randomized complete block design. Results show that yields of seeds selected through PPSM were significantly higher compared to seeds selected through FP, over both locations, on average, 7.4, 5.5 and 1.2 ton ha −1 for Granola G2 and G3, and the Atlantic, respectively. These yield increases represent an increase in the gross revenue of 30.8 to 51.8 million IDR ha −1 for Granola and 1.9 to 7.8 million IDR ha −1 for Atlantic at a farm gate price of 7, 000 and 6, 500 IDR kg −1, respectively. This study confirms that PPSM is superior to FP and improves the quality of the farms saved seeds.